Wheeling Charges Methodology for Deregulated Electricity Markets using Tracing-based Postage Stamp Methods - Hassan, M.Y.; Radzi, N.H.; Abdullah, M.P; Hussin, F.; Majid, M.S. (International Journal of Integrated Engineering, 2011)
MW-mile and Postage-stamp methods is traditionally used by electric utilities to determine a fixed transmission cost among users of firm transmission service. MW-Mile method is charging the users by determining the actual paths the power follows through the network. However, this method is not sufficient to recover the total transmission system cost. To recover the total transmission system cost, the Postage Stamp Method is adopted. This method is simple but its main drawback is that the charges paid by each user do not reflect the actual use of the network but based on the average usage of the entire network. This paper proposes a new wheeling charges methodology using tracing-based postage stamp methods. The proposed method allocates transmission costs among the generators proportional to the total power delivered to the load through transmission lines. The proposed method incorporates with generalised generation distribution factors to trace the contribution of each generator to the line flow. One unique feature of the proposed method is the consideration of the local load on the power flow allocation. Two case studies of 3-bus and IEEE 14-bus systems are used to illustrate the proposed method. Results show that the proposed method provides fair and equitable wheeling charges to generators reflecting the actual usage of the transmission system.